Improving the thermal stability of nanoporous metal electrode thin films for low temperature solid oxide fuel cells - Liu, Kang-Yu (2017)
Solid oxide fuel cells (SOFCs) are promising electrochemical devices for the production of electricity due to their high conversion efficiency, environmental friendly and fuel flexibility. Nevertheless, high operating temperature between 750-1000 °C provokes challenges of thermal management and material selection and limits their utility to large and stationary application. Thus lowering the operating temperature of SOFCs to intermediate temperature (500-750 °C) range or even below would greatly expand SOFCs technology to wider applications. Recent studies have shifted their focus to low-temperature solid oxide fuel cells (LTSOFCs) operating at temperatures below 500 °C. Utilizing nanoporous metal electrodes have been widely studied to replace ceramic electrode which is low electrocatalytically-active at such a low operation temperature. Platinum (Pt) is usually the most common choice as the cathode material for its superior catalytic activity towards oxygen reduction reaction (ORR) at a temperature lower than 500 °C. Typically a nanoporous Pt thin film cathode is often fabricated by sputtering at a high argon gas pressure to generate a high density of nanoscale pores or crack within the film to maximize the electrochemically active reaction sites, or the triple phase boundary (TPBs), where the gaseous fuel, catalytic electrode, and ion conductive electrolyte are in physical contact. The high density of reaction sites allows a high energy conversion rate with low electrode polarization, promising a high power output of the fuel cell. It has been reported that nanoporous Pt cathode can yield a high performance of 1.3 W/cm2 at 450 °C, an ultra-low operating temperature of 265 °C achieved 28 mW/cm2, and an ultra-low Pt loading of 0.02 mg/cm2 for potential applications. One key issue of using nanoporous Pt cathode for LTSOFCs is its poor thermal stability under high temperature operation. While the high density of nanopores or nanocracks can maximize the electrochemical active sites, the nanoscale feature is easily subjected to thermally-driven agglomeration to low surface free energy as per thermodynamic stability, which inevitably resulted in a rapid loss of the effective surface area and hence lowering fuel cell current output. The thermal agglomeration of a sputtered nanoporous Pt film is reported to initiate at around 300 °C, which is below the typical operating temperature of LTSOFCs between 350 to 500 °C. The irreversible deterioration to fuel cell performance due to thermal agglomeration of pure Pt cathode was reported by approximately 50% at 400 °C for 12 continuous hours of testing, which impedes the development of durable LTSOFCs. The preliminary study in this work also found 86.2% performance loss at 450 °C for 75 continuous hours of operation, and agglomeration occurred at the various site of the nanoporous Pt thin film cathode, including the unbounded surface, the bulk of the thin film, and cathode/electrolyte interface. The present work is dedicated to achieving a thermally stable nanoporous metal cathode with low performance degradation rate for LTSOFCs operating at a temperature of 300-500 °C, and addressing the improved thermal stability in terms of different agglomeration sites of nanoporous Pt cathode. Firstly, this work applied only few nanometers thin zirconia (ZrO2) capping on nanoporous Pt surface by atomic layer deposition (ALD) to serve as a geometrical confinement against thermal agglomeration, while an unexpected decrease in cathode polarization resistance was also observed. The thermal stability of the confined nanoporous Pt cathode and the origin of the enhanced cathode ORR were discussed. Secondly, the effectiveness of Ni alloyed Pt on hindering thermal agglomeration in bulk of nanoporous Pt thin film cathode was examined. The grain growth, which indicates the agglomeration of the Pt nanoparticles in bulk of thin film at elevated temperatures were compared between PtNi alloy and pure Pt metal to determine the impact of alloying on the thermal stability of the cathode. The performance of fuel cell and the electrochemical behavior using PtNi alloy cathode were also examined. Thirdly, a high energy O2 plasma etching technique was applied on the interface of Pt cathode/electrolyte to impede the thermal agglomeration of Pt at electrolyte contact side, where typically shows loss of TPBs from poor adhesion between Pt cathode and YSZ electrolyte. The morphological observation and adhesion measurement at cathode/electrolyte interface were investigated to elucidate the cause of O2 plasma etching to improved thermal stability. The fuel cell performance and cathode electrochemical performance over time were also examined. Lastly, three proposed methods were combined and strategized to obtain a highly thermal stable nanoporous metal cathode. Overall current stability of the cell with ALD-ZrO2 capped PtNi alloy cathode on O2 plasma etched electrolyte shows an ultra-low current degradation of 9.8% over 100 hours continuous operation at 450 °C. The proposed strategies ensured favorable nanoporous morphology of the film surface, constrained grain growth in bulk of film, and better contact of cathode to electrolyte at high temperature. The origin of improved thermal stability in terms of different agglomeration sites of nanoporous Pt cathode was: 1.) ALD-ZrO2 capping confines the surface agglomeration of the nanoporous Pt cathode and meanwhile facilitates the surface O2 adsorption-dissociation process; 2.) Ni alloyed Pt thin films constrains grain growth and maintains the porosity in bulk of cathode film for sufficient oxygen diffusion and adsorption-dissociation process; 3.) O2 plasma etching technique inhibits thermal agglomeration of Pt at YSZ electrolyte contact side and strengthens adhesion between Pt and YSZ which sufficiently retain the oxygen ion incorporation pathway.